Implementation of booth multiplier algorithm using Radix-4 in FPGA - Anis Shahida Mokhtar,; Chew, Sue Ping; Muhamad Faiz Md Din,; Nazrul Fariq Makmor,; Muhammad Asyraf Che Mahadi, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper presents the performance of Radix-4 Modified Booth Algorithm. Booth algorithm is a multiplication algorithm that multiplies two signed binary numbers in two's complement notation. Multiplier is a fundamental component in general-purpose microprocessors and in digital signal processors. With advances in technology, researchers design multipliers which offer high speed, low power, and less area implementation. Booth multiplier algorithm is designed to reduce number of partial products as compared to conventional multiplier. The proposed design is simulated by using Verilog HDL in Quartus II and implemented in Cyclone II FPGA. The result shows that the average output delay is 20.78 ns. The whole design has been verified by gate level simulation.